The Language Development (Vocabulary) Of Child Through The Expression Of The Image In Kindergarten Kemala Bhayangkari 90 Akpol Semarang - Utariningsih, Fitri; Handayani, Sri Sularti Dewanti (Jurusan PGPAUD FIP UNNES, 2016)
The purpose of this research is to find out how language development (vocabulary) of child through free and thematic images expression in kindergarten Kemala Bhayangkari 90 Akpol Semarang. This research uses the methods of Research and Development, but more focused on the development of activities to draw. The subject of the research is children aged 5-6 years. Based on the results of this research that is: 1) On free images, children already to draw in accordance with the wishes and imagination. The amount of the acquired vocabulary every child through free images increase from the previous image. 2) On thematic images, children are able to receive instructions and start to drawing in accordance with the specified theme. Creativity appear when children add another shape on the thematic images. The amount of the acquired vocabulary every child through free images is fluctuative. 3) In general the free of image tend to have the same characteristics, namely the children love to draw the object people, houses, trees, the sun, the moon, and environment/ place. 4) The results of the free and thematic images shows that free images, more effective in boosting the development of the language (vocabulary). This is because a free image more gives children the opportunity to draw according to the wishes and stories presented are also more free and expressive.